Divorce by Mutual Consent - Patel, Vijay (International Journal of Law, Human Rights and Constitutional Studies; Vol 1 No 1&2 (2019): International Journal of Law, Human Rights and Constitutional Studies, 2019)
This study would focus on marriage and the freedom from it, i.e. divorce by mutual consent. Divorce, on the other hand, is a difficult subject. Divorce was prohibited by Hindu law, save in select communities, primarily in the lower socioeconomic strata, where it was authorized by custom; therefore there was strong opposition to any provision for divorce in the new legislation that was being drafted. Marriage is a sacred commitment to be taken and never to be freed from till the death of one of the spouses, as written in our rituals and observed by Hindus as their belief. However, new circumstances had developed, necessitating the development of fair and equitable remedies in the case of concerns damaging the environment. How to cite this article: Patel V. Divorce by Mutual Consent. Int Jour Law Hum Rights Const Stud 2021; 2(1): 1-4.